2017
DOI: 10.1111/srt.12373
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ageing biomarkers in human dermis biopsies by thermal analysis (DSC) combined with Fourier transform infrared spectroscopy (FTIR/ATR)

Abstract: DSC and FTIR are well-suited techniques to characterize human skin, giving accurate results with a high reproducibility. The combination of these techniques is useful for a better understanding of human skin modifications with intrinsic and extrinsic ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 41 publications
6
30
0
Order By: Relevance
“…The dermis is a connective tissue containing high levels of extracellular matrix proteins, mainly collagens, elastin, and glycosaminoglycan (GAG). Collagen I, which represents around 90% of collagen fibrils, decreases with aging, due to a lower synthesis level and a higher matrix degradation . Collagen degradation can be caused either by direct UV absorption or through matrix metalloproteinase activities .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The dermis is a connective tissue containing high levels of extracellular matrix proteins, mainly collagens, elastin, and glycosaminoglycan (GAG). Collagen I, which represents around 90% of collagen fibrils, decreases with aging, due to a lower synthesis level and a higher matrix degradation . Collagen degradation can be caused either by direct UV absorption or through matrix metalloproteinase activities .…”
Section: Introductionmentioning
confidence: 99%
“…Collagen degradation can be caused either by direct UV absorption or through matrix metalloproteinase activities . Differences between photoaging and chronological aging have been observed on collagen fibers’ structure: These fibers are thickened and fragmented on photo‐exposed areas, while they appear more stable on skin subjected only to chronological aging . Another feature of photoaging is the increase of GAG proportion in the dermis …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,6,7 Nevertheless, due to multifactorial and slowness of the aging processes, that leads to subtle changes of biological function (including biochemical, morphological, physical aspects) complementary studies on aging are still of interest. [8][9][10][11] In a previous work, 12 we showed that Differential Scanning Calorimetry (DSC) was a powerful technique to evaluate the hydric…”
Section: Introductionmentioning
confidence: 99%